MASA KEJAYAAN PENDIDIKAN ISLAM - Riyanti Riyanti; Alya Nurul Fatwa; Nilam Sari; Tiara Alia; Sriliza (CV. ADIBA AISHA AMIRA, 2026)
The golden age of Islamic education represents a significant period in the history of Islamic civilization, marked by the rapid development of educational institutions and systems. During this era, education was not limited to religious studies but also integrated scientific and intellectual disciplines such as mathematics, medicine, astronomy, philosophy, and natural sciences. Educational institutions such as mosques, madrasas, Bayt al-Hikmah, and libraries functioned as centers of learning and knowledge production. Government support, particularly from caliphs and Muslim rulers, played a crucial role in providing facilities, funding, and protection for scholars and scientists. The integration of religious knowledge and scientific inquiry gave rise to prominent Muslim intellectuals who made substantial contributions to the advancement of knowledge and global civilization. Therefore, the golden age of Islamic education had a profound impact on the development of science, culture, and human civilization worldwide.